Infectious mononucleosis: atypical manifestation - V. A. Greshnyakova; L. G. Goriacheva; A. O. Nikiforova (LLC "Diagnostics and Vaccines", 2022)
In most cases, EBV mononucleosis in hospitalized children occurs in a typical form, with a classical clinical picture. Cases of hepatitis, as the leading syndrome in EBV infection, are extremely rare. The article presents a clinical case of atypical onset of infectious mononucleosis of EBV etiology, which started with liver damage syndrome. This clinical experience gives an opportunity to run diagnostics of herpesvirus infections in cases of nonspecific liver damage.